Handling Off-Task Behavior in Elementary School Students with Self-Management - Lestari, Angelina Kartini Agung; Suminar, Dewi Retno (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Off-task behavior is the behavior of students spending most of the time to engage in behaviors that are not learning and individuals spend less time on the task or learning process. Symptoms appear in aspects of overt behavior such as making excessive movements that are not related to academic activities; issuing sentences/words outside the context of learning activities; choosing not to engage in a learning activity that is happening in learning. This study aims to evaluate the effectiveness of self-management to reduce off-task behavior. The participant of this study was a 3rd grade elementary school, he is a boy student who had low resilience in doing assignments and diverted to non-academic activities such as sleeping, playing with stationery, leaving the class to go to the toilet, playing with spit, biting fingers, daydreaming, and putting stationery in the mouth. The assessment conducted was an interview, behavioral observational of students in schools (BOSS), Wechsler Intelligence Scale for Children (WISC), Child Behavior Checklist (CBCL), Draw a Person (DAP), and House Tree Person (HTP). The results showed that the participants avoided doing tasks for a long duration and experienced problems in attention in class. The intervention consisted of four treatments with 16 sessions to reduce off-task behavior, so that on-task behavior increased. The result is that self-mangament intervention is effective in reducing the duration of off-task time, the subject can complete all his assignments to completion. Perilaku off-task adalah perilaku siswa menghabiskan sebagian besar waktu untuk terlibat dalam perilaku yang bukan belajar dan individu menghabiskan lebih sedikit waktu pada tugas atau proses belajar. Gejala muncul pada aspek perilaku yang tampak seperti melakukan gerakan berlebihan yang tidak terkait dengan kegiatan akademik; mengeluarkan kalimat/ kata-kata diluar konteks aktivitas pembelajaran; memilih untuk tidak terlibat dalam suatu aktivitas pembelajaran yang sedang terjadi dalam pembelajaran. Penelitian ini bertujuan untuk melihat efektifitas self-management menurunkan perilaku off-task. Partisipan penelitian ini adalah seorang siswa laki-laki sekolah dasar kelas 3 yang memiliki ketahanan rendah dalam mengerjakan tugas dan mengalihkan pada kegiatan diluar akademik seperti tidur, bermain alat tulis, meninggalkan kelas untuk pergi ke toilet, memainkan ludah, menggigit jari, melamun, dan memasukan alat tulis kedalam mulut. Asesmen yang dilakukan adalah wawancara, behavioral observational of students in schools (BOSS), Wechsler Intelligence Scale for Children (WISC), Child Behavior Checklist (CBCL), Draw a Person (DAP), dan House Tree Person (HTP). Hasil menunjukan partisipan menghindari pengerjaan tugas dengan durasi yang lam dan mengalami permasalahan dalam atensi di kelas. Intervensi terdiri dari empat perlakuan dengan 16 sesi untuk menurunkan perilaku off-task, sehingga perilaku on-task meningkat. Hasilnya intervensi self-mangament efektif menurunkan durasi waktu off-task, subjek dapat menyelesaikan semua tugasnya hingga tuntas.